2021
DOI: 10.21037/atm-20-7155
|View full text |Cite
|
Sign up to set email alerts
|

Plasma EGFR mutation abundance affects clinical response to first-line EGFR-TKIs in patients with advanced non-small cell lung cancer

Abstract: Background: Activated epidermal growth factor receptor (EGFR) mutation is the main pathogenic cause of non-small cell lung cancer (NSCLC) in Asia. However, the impact of plasma EGFR mutation abundance, especially of the ultra-low abundance of EGFR mutation detected by highly sensitive techniques on clinical outcomes of first-line EGFR tyrosine kinase inhibitors (TKIs) for advanced NSCLC patients remains unclear.Methods: We qualitatively detected baseline EGFR status of NSCLC tissues using amplification-refract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In addition, a retrospective study by Tan et al ( 40 ) demonstrated that the co-existence of uncommon EGFR mutations and TP53 mutations is associated with a shorter PFS. By contrast, Canale et al ( 41 ) observed significantly shorter PFS and OS times in the subgroup of TKI-treated patients with EGFR exon 19 deletion compared with those without this deletion, whilst Wang et al ( 42 ) identified no significant difference in PFS between patients with EGFR exon 19 deletion and EGFR L585R mutations. Such evidence is not sufficient to completely clarify the intrinsic association between TP53 mutations and EGFR -TKI efficacy.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, a retrospective study by Tan et al ( 40 ) demonstrated that the co-existence of uncommon EGFR mutations and TP53 mutations is associated with a shorter PFS. By contrast, Canale et al ( 41 ) observed significantly shorter PFS and OS times in the subgroup of TKI-treated patients with EGFR exon 19 deletion compared with those without this deletion, whilst Wang et al ( 42 ) identified no significant difference in PFS between patients with EGFR exon 19 deletion and EGFR L585R mutations. Such evidence is not sufficient to completely clarify the intrinsic association between TP53 mutations and EGFR -TKI efficacy.…”
Section: Discussionmentioning
confidence: 94%
“…Previous study has shown that highly abundant EGFR mutations in pretreatment blood samples predicted longer PFS on EGFR-TKIs in advanced NSCLC patients. 23 More studies are needed to establish the efficacy of osimertinib for NSCLC patients with EGFR fusions in either first- or second-line treatment. Interestingly, histology on biopsies revealed the gradual development of SCC transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 presents data on the association between plasma ctDNA/cfDNA EGFR mutations and the efficacy and prognosis of targeted therapy in NSCLC patients [ 28 , 30 , 31 , 32 , 33 , 34 , 35 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. The BENEFIT trial prospectively demonstrated the feasibility of using liquid biopsy to guide the efficacy of first-line EGFR-TKI therapy for the first time.…”
Section: Plasma Ctdna-based Egfr Mutations Can Guide Targeted Therapy...mentioning
confidence: 99%
“…The median PFS was also significantly longer in patients with a plasma EGFR mutation abundance of >0.1% compared to that of patients with a plasma EGFR mutation abundance of 0.01–0.1% ( p = 0.0115). Additionally, one Cox multivariate analysis indicated that mutation abundance in plasma was an independent predictor of PFS (HR = 2.41, 95% CI = 1.12–5.20; p = 0.025) [ 55 ]. In another study, researchers used a modified semi-quantitative method (reformed-superARMS) based on ΔCt values that were generated during polymerase chain reaction (PCR) assays to investigate the impact of different baseline ctDNA EGFR mutation levels and changes in ctDNA EGFR mutations with reformed-superARMS on the outcomes and prognoses of patients receiving targeted therapy.…”
Section: Plasma Ctdna-based Egfr Mutations Can Guide Targeted Therapy...mentioning
confidence: 99%